KNOWLEDGE MANAGEMENT AS ONE OF OPEN EDUCATION TECHNOLOGIES’ DEVELOPMENT DIRECTIONS - Yury A. Kravchenko (Открытое образование (Москва), 2016)
The article deals with the problem of creating knowledge management scenarios as the principal organization of information processes in the open education technologies, as well as the principles of their design and evolution. Solution the problem of information overfl ow in intelligent learning systems was described from the point of transition from the storage and processing of data to the accumulation and processing of knowledge. Increase the probability of producing new knowledge in learning is expected due to the use of interdisciplinary and multidisciplinary approaches to gathering information. Fuzzy forecast model of the student’s knowledge level estimation was proposed, taking into account the natural loss of some knowledge for a long time period.